Global attractors for semigroup actions on uniformizable spaces. Issue 1 (2nd January 2020) - Souza, Josiney A.; Alves, Richard W. M.
ABSTRACT: In this paper the notion of global attractor is extended from the setting of semigroup actions on metric spaces to the setting of semigroup actions on uniformizable spaces. General conditions for the existence of global attractor are discussed and its relationship with the global uniform attractor is presented.